PENGARUH METODE DEMONSTRASI DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR BAHASA INGGRIS SISWA - Diana Ratna Dewi; Ali Sukamtono; Dian Triana (FAI- Undar, 2017)
The purpose of this research is to analyze the influence teaching methods and study motivation towards students achievement class VII at Islamic Junior State High School of Caruban. The population and sample in this research is all 37 students as respondent.Design of this research is quantitative research because testing relationship between three variables, there are teaching methods, study motivation and students achievement. Collecting data methods using questionnaire which is given to the students class VII at Islamic Yunior High School of Caruban as the respondents . It is analyzed using Multiple linear regression and procced with 17th version of SPSS software.The results of this study indicate that: (1) positive significant (p=0,00) the influence teaching methods towards students achievement class VII at Islamic Yunior High School of Caruban , with equality Y = 30.481 + 0.784X(2) positive significant (p=0,00), the influence student motivation towards students achievement class VII at Islamic Yunior State High School of Caruban with equality Y = 31.340 + 0.642X X2 (3) positive significant simultanly (p=0,00) the influence teaching methods and study motivation towards students achievement class VII at Islamic Yunior High School of Caruban 85,4% with equality Y = 29.766 + 0.346X1 + 0.357X2Based on these results, the authors give advice to all teachers in Islamic Yunior High School of Caruban Madiun be more creative and variety in making or creating a learning method for students. It make the students learning fun. The most important thing is give more motivation for students to following teaching learning Process.